1996
DOI: 10.1021/jp9613549
|View full text |Cite
|
Sign up to set email alerts
|

Langmuir Trough Study of Surfactant Mixtures Used in the Production of a New Ultrasound Contrast Agent Consisting of Stabilized Microbubbles

Abstract: Span-type surfactants (sorbitan fatty acid esters) and Tween-type surfactants (sorbitan polyoxyethylene fatty acid esters) are employed by us to generate stabilized microbubbles for use in diagnostic ultrasound. After sonication of an aqueous surfactant solution, only some mixtures of Span-type and Tween-type surfactants at certain conditions can form stable microbubbles. This work investigated the stability of the surfactant-stabilized microbubbles by using a Langmuir trough to measure the π-A isotherms of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 17 publications
0
35
0
Order By: Relevance
“…There are thought to be several reasons for this. First, as above, previous studies have indicated that sonication may produce a chemical change in the coating material, which improves stability [48]. Second, a much higher concentration of microbubbles was produced and the dissolved gas concentration in the liquid would also have been higher on account of the entrainment of gas throughout the processing volume during sonication.…”
Section: Stabilitymentioning
confidence: 84%
See 1 more Smart Citation
“…There are thought to be several reasons for this. First, as above, previous studies have indicated that sonication may produce a chemical change in the coating material, which improves stability [48]. Second, a much higher concentration of microbubbles was produced and the dissolved gas concentration in the liquid would also have been higher on account of the entrainment of gas throughout the processing volume during sonication.…”
Section: Stabilitymentioning
confidence: 84%
“…In addition, the high temperatures and pressures generated by inertial cavitation in the liquid may result in chemical modification of the coating material that further enhances stability, although this depends upon the individual surfactant [48]. The size distribution of the microbubbles produced depends upon the frequency, power and pulse regime of the ultrasound, although there is no simple theoretical relationship between these variables and fabrication protocols are developed empirically [20].…”
Section: Sonicationmentioning
confidence: 99%
“…An encapsulation stabilizes a bubble by various mechanisms; Wang et al suggested three-reduced surface tension, increased resistance to gas permeation and surface hardening [12,13]. The first two effects have been modeled [10].…”
Section: Introductionmentioning
confidence: 99%
“…[7,15] Previous papers have reported dissolution rates of bubbles several tens of micrometers in radius using optical microscopy. [10,16] In these studies, the bubbles were immobilized on a surface or at the extremity of a pipet, which can influence the shedding of the phospholipid's wall significantly.…”
mentioning
confidence: 99%